2021
DOI: 10.1038/s41467-021-21480-1
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the structural complexity of glycolipids with cryogenic infrared spectroscopy

Abstract: Glycolipids are complex glycoconjugates composed of a glycan headgroup and a lipid moiety. Their modular biosynthesis creates a vast amount of diverse and often isomeric structures, which fulfill highly specific biological functions. To date, no gold-standard analytical technique can provide a comprehensive structural elucidation of complex glycolipids, and insufficient tools for isomer distinction can lead to wrong assignments. Herein we use cryogenic gas-phase infrared spectroscopy to systematically investig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 53 publications
1
48
0
3
Order By: Relevance
“…Since first being published, the program has already been applied for a diverse number of projects, e.g., the large scale conformer generation of organometallic compounds, 183,590 protein side chain conformational sampling, 591 gas docking in metal-organic frameworks (MOF), 444 input generation of machine-learning approaches, 414 and various other mechanistic, 592-594 conceptual, [595][596][597][598] and spectroscopic studies. 22,476,[599][600][601] In Part III, a recent extension to the CREST code was presented and discussed linking the conformational low-energy chemical space to statistical thermodynamics. The central quantity here is the absolute molecular entropy, or more specifically, the conformational contribution to it.…”
Section: Final Summary and Conclusionmentioning
confidence: 99%
“…Since first being published, the program has already been applied for a diverse number of projects, e.g., the large scale conformer generation of organometallic compounds, 183,590 protein side chain conformational sampling, 591 gas docking in metal-organic frameworks (MOF), 444 input generation of machine-learning approaches, 414 and various other mechanistic, 592-594 conceptual, [595][596][597][598] and spectroscopic studies. 22,476,[599][600][601] In Part III, a recent extension to the CREST code was presented and discussed linking the conformational low-energy chemical space to statistical thermodynamics. The central quantity here is the absolute molecular entropy, or more specifically, the conformational contribution to it.…”
Section: Final Summary and Conclusionmentioning
confidence: 99%
“… 39 In agreement with this result, the analysis of lipid granules ( Figure S7b, d ) identifies, among the components relevant for the discrimination, the 1065 cm –1 peak, which has been assigned to glycolipids. 40 In addition, the major constituents of tears are glycoproteins (e.g., IgA, lactoferrin, and lacritin), 41 and protein glycosylation has been found altered in patients affected by different neurodegenerative disorders, including Huntington’s, Alzheimer’s, and ALS diseases. 42 …”
Section: Resultsmentioning
confidence: 99%
“…Because the harmonic approximation systematically overestimates vibrational frequencies, the computed IR spectra were scaled by single-parameter frequency scaling to enhance the agreement between experiment and theory. The harmonic frequencies were corrected by a scaling factor of 0.965, which has proven accuracy in numerous previous studies on various molecular classes including nucleotides [ 40 ], sugars [ 41 , 51 , 52 ], and lipids [ 36 , 37 ] with comparable methods as used in this work. The harmonic free energies ΔF were calculated at 90 K, according to the temperature in the ion trap.…”
Section: Methodsmentioning
confidence: 99%
“…Cryogenic gas-phase infrared (IR) spectroscopy was recently established as a powerful technique to resolve minute structural differences in sphingolipid and glycolipid isomers [ 36 , 37 ]. Motivated by one of these previous studies, which showed that both C=C location and configuration in protonated deoxysphingolipids are distinguishable without chemical modification by gas-phase IR spectroscopy [ 36 ], we extended the application to FAs in this work.…”
Section: Introductionmentioning
confidence: 99%